2022
DOI: 10.1007/s00402-022-04634-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survivorship of an exchangeable-neck hip prosthesis with a Ti-alloy/Ti-alloy neck–stem junction

Abstract: Introduction Breakage of exchangeable-neck (EN) and adverse local tissue reactions (ALTRs) to neck–stem junction (NSJ) damage products are responsible for increasing the revision rate of EN hip prostheses. We investigated the survivorship of an EN hip prosthesis including a NSJ with both components made of titanium alloy (Ti-alloy/Ti-alloy) to assess whether, and to what extent, EN breakage and NSJ damage affected implant survivorship. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A recent study using the data from an Italian hip replacement registry analysed 2857 DM femoral stem THA performed between January 2000 and December 2009 [ 14 ]. The patients were treated with AncaFit (Cremascoli Ortho, S.r.l, Milan, Italy) hip prosthesis, the forerunner of DM stem THA system (Wright Medical Technology) investigated in this study with identical neck-stem coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using the data from an Italian hip replacement registry analysed 2857 DM femoral stem THA performed between January 2000 and December 2009 [ 14 ]. The patients were treated with AncaFit (Cremascoli Ortho, S.r.l, Milan, Italy) hip prosthesis, the forerunner of DM stem THA system (Wright Medical Technology) investigated in this study with identical neck-stem coupling.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the 17-year survival rates for any reason and aseptic loosening of any components were 88.9%. With only 2 cases of modular neck breakage and one case of ALTR identified, the authors concluded that the risk of modular neck breakage is lower than previously reported and that the incidence of neck-stem junction damage products does not significantly alter the rate of implant loosening [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the micromovement within the junction is one of the key factors affecting MACC, along with the implantation time, the stress level within the Ti-alloy, and interface friction conditions [ 23 , 24 , 25 , 26 , 27 ]. The occurrence of MACC may promote the release of metal debris in the periprosthetic tissues or ion release at the systemic level [ 5 , 28 , 29 ], thus increasing the risk of implant failure [ 3 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modular neck stems were introduced to hip endoprosthesis with the expected benefits of reducing pain and improving the range of motion and leg length [1][2][3]. Besides classic stems (Figure 1a,c), Wright Medical Technology/Microport, Stryker, Depuy, Lima Corporate, Zimmer, Adler Ortho, Cremasoli, and others are recognized worldwide manufacturers of modular neck stems (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Ti6Al4V and stems from the same alloy has generated interest in recent years because the various neck sizes, offsets, lengths, and design configurations allow the surgeon to optimize the range of motion and the patient's leg length. However, there have been concerns due to early in vivo fractures as well as adverse tissue reactions related to corrosion at the neck-stem interface [2][3][4][5][6][7][8][9][10][11]. The presence of the neck-stem interface using titanium alloys makes the neck junction vulnerable to fretting, corrosion, and fatigue fracture.…”
Section: Introductionmentioning
confidence: 99%